How can we maximize the diagnostic utility of uroflow?: ICI‐RS 2017. (9th January 2018) - Gammie, Andrew; Rosier, Peter; Li, Rui; Harding, Chris
Abstract : Aims: To gauge the current level of diagnostic utility of uroflowmetry and to suggest areas needing research to improve this. Methods: A summary of the debate held at the 2017 meeting of the International Consultation on Incontinence Research Society, with subsequent analysis by the authors. Results: Limited diagnostic sensitivity and specificity exist for maximum flow rates, multiple uroflow measurements, and flow‐volume nomograms. There is a lack of clarity in flow rate curve shape description and uroflow time measurement. Conclusions: There is a need for research to combine uroflowmetry with other non‐invasive indicators. Better standardizations of test technique, flow‐volume nomograms, uroflow shape descriptions, and time measurements are required.